From non-place to place in post-suburbia: city-edge office parks as loci for nature-based micro-interventions. Issue 13 (9th November 2020) - Mallo, Daniel; Schoneboom, Abigail; Tardiveau, Armelle; Vigar, Geoff
Abstract : City-edge office parks are a significant, and under-researched, urban phenomenon. Indeed the transformation of these environments to better address social and environmental sustainability criteria has been described as 'the big project for this century'. While top-down 'retrofitting' is the dominant approach to such transformation, in this paper we highlight the limitations of such an approach and argue for the potential of more bottom-up and creative methods. We report on experiments with office park employees to address the 'placelessness' of such environments, aimed at improving ecological sustainability and individuals' health and wellbeing. We make three significant conclusions: a wealth of hidden ecological and social assets exist to be exploited in such environments; creative methods to envision more sustainable future s have a great deal of potential to break existing path dependencies; and, respecting participation constraints among employee-participants is vital for future research and action.